Pertumbuhan Tanaman Sawi Caisim (Brassica Juncea l.) Secara Hidroponik Pada Media Pupuk Organik Cair Dari Kotoran Kelinci Dan Kotoran Kambing. - AMITASARI, AMITASARI, Dra. Suparti, M.Si (2016)
Organic fertilizer is commonly used for goat droppings. Other livestock manure that has potential as an untapped organic fertilizer is rabbit droppings. Mustard production has decreased every year, due to the lack of area and how the cultivation of less than the maiximum, it would require the cultivation of mustard efficient way and the right fertilizer is hydroponics using organic fertilizers. The purpose of this study was to determine the growth of hydroponic lettuce in the media caisim organic fertilizer from rabbit droppings and goat manure.This study was conducted in Laboratory Green House Biology Education Teacher Training and Science Faculity Education Muhammadiyah University of Surakarta. The method used in the study is an experimental method by using a completely randomized design (RAL) one factor, namely the treatment of liquid organic fertilizer rabbit dropphings 500 ml and liquid organic of goat manure 500 ml. Data were analyzed with descriptive analysis shows that the media's treatment of liquid manure rabbit droppings and goat dung to give effect to the growth of plant height and number of leaves. The best treatment fot stem height is P2 (goat manure liquid 500 ml) of 1,3 cm, while the best treatment for a number of leaves is P1 (rabbit dropping liquid 500 ml) at 5 leaves.